2012
DOI: 10.1371/journal.pone.0042541
|View full text |Cite
|
Sign up to set email alerts
|

Store-Operated Ca2+ Entry Is Remodelled and Controls In Vitro Angiogenesis in Endothelial Progenitor Cells Isolated from Tumoral Patients

Abstract: BackgroundEndothelial progenitor cells (EPCs) may be recruited from bone marrow to sustain tumor vascularisation and promote the metastatic switch. Understanding the molecular mechanisms driving EPC proliferation and tubulogenesis could outline novel targets for alternative anti-angiogenic treatments. Store-operated Ca2+ entry (SOCE), which is activated by a depletion of the intracellular Ca2+ pool, regulates the growth of human EPCs, where is mediated by the interaction between the endoplasmic reticulum Ca2+-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
245
2
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(269 citation statements)
references
References 100 publications
19
245
2
3
Order By: Relevance
“…Thus, abnormalities in the expression and/or function of STIM1 and ORAI1, which were shown to mediate VEGFevoked calcium entry promoting EC migration, tube formation and angiogenesis [91], and might be involved in the enhancing the pro-angiogenic response of ECs in tumours (figure 4). Indeed, upregulated mRNA and protein levels of ORAI1, STIM1 and TRPC1 (which is also known to contribute to SOCE) accompanied by the increase in CAI-sensitive SOCE were detected in endothelial progenitor cells from patients with renal cellular carcinoma [96].…”
Section: Ca 2þ Remodelling In Tumour Vascularizationmentioning
confidence: 99%
“…Thus, abnormalities in the expression and/or function of STIM1 and ORAI1, which were shown to mediate VEGFevoked calcium entry promoting EC migration, tube formation and angiogenesis [91], and might be involved in the enhancing the pro-angiogenic response of ECs in tumours (figure 4). Indeed, upregulated mRNA and protein levels of ORAI1, STIM1 and TRPC1 (which is also known to contribute to SOCE) accompanied by the increase in CAI-sensitive SOCE were detected in endothelial progenitor cells from patients with renal cellular carcinoma [96].…”
Section: Ca 2þ Remodelling In Tumour Vascularizationmentioning
confidence: 99%
“…Using knockdown and overexpression tools, the authors showed that STIM1 regulates VEGF secretion as well as in vivo tumor angiogenesis in mice (17). Sanchez-Hernandez et al (87) assessed SOCE in EPCs and later on characterized the SOCE players in EPCs derived from renal carcinoma (RCC-EPCs) blood samples (63). The authors further established that STIM1 and Orai1 regulate RCC-EPCs SOCE, proliferation, and tubulogenesis (63).…”
Section: Tumor Angiogenesismentioning
confidence: 99%
“…Sanchez-Hernandez et al (87) assessed SOCE in EPCs and later on characterized the SOCE players in EPCs derived from renal carcinoma (RCC-EPCs) blood samples (63). The authors further established that STIM1 and Orai1 regulate RCC-EPCs SOCE, proliferation, and tubulogenesis (63). Interestingly, STIM1 and Orai1 expression was higher in RCCEPCs compared with normal EPCs, which in turn resulted in elevated SOCE and angiogenesis (63).…”
Section: Tumor Angiogenesismentioning
confidence: 99%
“…Similarly to HUVEC, suppression of ORAI1 in endothelial progenitor cells (EPCs) prevents VEGF-mediated SOCE and tubule formation (22,56). Moreover, EPCs isolated from RCC patients (RCC-EPCs) display an increased SOCE, which correlates with ORAI1, STIM1, and TRPC1 overexpression when compared with EPCs from healthy patients: genetic suppression of STIM1, ORAI1, and TRPC1 affects SOCE in RCC-EPCs (59). It has to be noted that the role of ORAI1 in ECs has been questioned by Antigny et al (4), although they described STIM1 as a key player (together with TRPC1 and TRPC4) in tube formation in both HUVEC and EA.hy926 cells.…”
Section: Inducing Angiogenesismentioning
confidence: 99%